2019
DOI: 10.3389/fimmu.2019.02589
|View full text |Cite
|
Sign up to set email alerts
|

Secondary C1q Deficiency in Activated PI3Kδ Syndrome Type 2

Abstract: Monogenic forms of vasculitis are rare but increasingly recognized. Furthermore, genetic immunodeficiency is increasingly associated with inflammatory immune dysregulatory features, including vasculitis. This case report describes a child of non-consanguineous parents who presented with chronic digital vasculitis early in life, is of short stature, has facial dysmorphia, immunodeficiency (low serum IgA, high serum IgM), recurrent bacterial infections, lymphoproliferation, absence of detectable serum C1q, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Increased IgM levels were observed in most (58%) but not all patients. 6 During the last decade, Cases of APDS2 keep reported in the literature [7][8][9][10][11][12][13][14][15][16][17] with very heterogenous clinical phenotypes as shown in this case report of four members of the same family (parents and 2 siblings). While the youngest child presented early in life with marked lymphoproliferation and died later due to EBV-induced diffuse large B cell lymphoma complications, the other sibling and parents had a milder course with recurrent sinopulmonary infections and mild adenotonsillar hypertrophies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Increased IgM levels were observed in most (58%) but not all patients. 6 During the last decade, Cases of APDS2 keep reported in the literature [7][8][9][10][11][12][13][14][15][16][17] with very heterogenous clinical phenotypes as shown in this case report of four members of the same family (parents and 2 siblings). While the youngest child presented early in life with marked lymphoproliferation and died later due to EBV-induced diffuse large B cell lymphoma complications, the other sibling and parents had a milder course with recurrent sinopulmonary infections and mild adenotonsillar hypertrophies.…”
Section: Discussionmentioning
confidence: 79%
“…14 Congenital infections are also reported, as shown in this case report describing disseminated and congenital toxoplasmosis in a mother and child who share a pathogenic mutation in PIK3R1. 32 Chronic digital vasculitis, 17 short stature and failure to thrive, 11,12,14 microcephaly, 10 and other minor facial dysmorphology 14 were reported as associated findings with APDS2. Another rare but significant clinical phenotype that can be associated with mutations in the PIK3R1 gene is Short Syndrome (short stature, hyperextensibility, hernias, ocular depression [deeply set eyes], Rieger anomaly, teething delay, partial lipodystrophy, insulin resistance, and facial dysmorphic signs).…”
Section: Discussionmentioning
confidence: 99%
“…How these two phenomena may be pathologically linked is unknown. Another report of HIGM and acquired C1q deficiency in activated phosphoinositide 3-kinase delta syndrome (APDS) speculated that increased apoptotic bodies may be a possible mechanism for increased consumption of C1q complement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous resolution of the vasculitis was observed similar to the clinical course of uncomplicated primary cutaneous vasculitis (47) though ANCA positivity remained, indicating that the presence of autoantibodies alone is insufficient for disease manifestation. However, in APDS patients with complicated or systemic vasculitic features, immunomodulatory regimens, such as corticosteroids, hydroxychloroquine, azathioprine, mycophenolate, and cyclophosphamide, have been utilized with variable results (38,(40)(41)(42). In one such case, targeting mTOR hyperactivity with sirolimus allowed for improved management of the associated autoimmune vasculitis (41).…”
Section: Discussionmentioning
confidence: 99%
“…As noted in Table 2, vasculitis is an infrequent autoimmune feature amongst APDS patients. In 2019, Hong et al reported chronic vasculitis affecting the fingers and toes of a pediatric APDS2 patient who was interestingly found to have a C1q deficiency secondary to increased consumption rather than intrinsic production defect or anti-C1q antibodies (40). The etiology of vasculitis was postulated to be secondary to low C1q similar to the lupus-like vasculitis seen in genetic C1q deficiency (43).…”
Section: Apds: Autoimmune Clinical Manifestationsmentioning
confidence: 99%